Commercial lobbying in Australia: exploring the Australian lobby register - Halpin, Darren; Warhurst, John (2016)
Politicians and policy makers routinely engage with lobbyists and see them as crucial agents in the political process. But how much do we really know about the Australian lobby system? Although there are a range of reviews of lobby regulation schemes and discussions about the work of lobbyists, a comprehensive contemporary picture of the commercial lobbying system in Australia is missing. Using data from the federal lobby register, this article sets out to map the commercial lobbying scene at the national level. Using this as a backdrop, the article goes on to discuss what questions this raises and how we might develop a deeper understanding of the commercial lobbying system in Australia. - Reproduced. 11
Keywords: Pressure groups - Australia; Pressure groups